Vesatolimod, a Toll-like Receptor 7 Agonist, Induces Immune Activation in Virally Suppressed Adults Living With Human Immunodeficiency Virus–1. (12th October 2020) - Riddler, Sharon A; Para, Michael; Benson, Constance A; Mills, Anthony; Ramgopal, Moti; DeJesus, Edwin; Brinson, Cynthia; Cyktor, Joshua; Jacobs, Jana; Koontz, Dianna; Mellors, John W; Laird, Gregory M; et al.
Abstract: Background: Treatment with vesatolimod, an investigational, oral, toll-like receptor 7 (TLR7) agonist, leads to sustained viral remission in some non-human primates when combined with anti-envelope antibodies or therapeutic vaccines. We report results of a Phase Ib study evaluating safety, pharmacokinetics, and pharmacodynamics of vesatolimod in adults living with human immunodeficiency virus (HIV)–1. Methods: In this double-blind, multicenter, placebo-controlled trial, participants on antiretroviral therapy with screening plasma HIV-1 RNA levels <50 copies/mL were randomized (6:2) to receive 6–10 doses of vesatolimod (1–12 mg) or matching placebo orally every other week in sequential dose-escalation cohorts. The primary study objectives included establishing the safety and virologic effects of vesatolimod (change from baseline in plasma HIV-1 RNA). Pharmacokinetics and pharmacodynamic/immunologic activity were assessed as secondary objectives. Results: A total of 48 individuals were randomly assigned to vesatolimod (n = 36) or placebo (n = 12). Vesatolimod was generally well tolerated, with no study drug–related serious adverse events or adverse events leading to study drug discontinuation. There were no statistically significant changes from baseline in plasma HIV-1 RNA in the vesatolimod groups, compared to placebo. Vesatolimod plasma exposures increased dose proportionally; consistent responses in cytokines, interferon-stimulated gene expression, and lymphocyte activation were observed with increasing dose levels above 4 mg. Peak elevations 24 hours after receipt of a 6 mg dose were >3.9-fold higher for interferon gamma-induced protein 10 (IP-10), interleukin-1 receptor antagonist (IL-1RA), interferon–inducible T-cell alpha chemoattractant (ITAC) when compared to baseline values. Conclusions: Vesatolimod was well tolerated at doses ranging from 1 to 12 mg. Immune stimulation was observed at doses above 4 mg, providing rationale for future combination trials in people living with HIV. Clinical Trials Registration: NCT02858401. Abstract : Vesatolimod was safe and well tolerated in antiretroviral therapy–suppressed individuals living with human immunodeficiency virus (HIV). Vesatolimod showed consistent immunomodulatory effects that, together with other virus-targeting approaches, may aid the development of a curative treatment strategy for HIV infection.